The Three Neighbors in The Room: A Study of Harold Pinter - Mujtaba Mohammedali Yahya Al-Hilo (RIRAI Publisher, 2023)
In order to analyze Harold Pinter’s, play The Room, this essay examines the importance of Slavoj Zizek's three sorts of neighbor theory. The play's social relationships and power structures are insightfully interpreted in this essay by considering the play's characters and themes through the eyes of the play's imagined, symbolic, and real neighbors. The play The Room is more than simply a portrayal of social connections, the paper says, but a complex examination of the ways in which power, desire, and suffering interact in the human experience. Zizek's theory provides a helpful framework for evaluating the play's issues and repercussions.